2020
DOI: 10.1111/tpj.15049
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene‐activated PpERF105 induces the expression of the repressor‐type R2R3‐MYB gene PpMYB140 to inhibit anthocyanin biosynthesis in red pear fruit

Abstract: SummaryEthylene induces anthocyanin biosynthesis in most fruits, including apple (Malus domestica), strawberry (Fragaria × ananassa), and plum (Prunus spp.). However, ethylene inhibits anthocyanin biosynthesis in pear (Pyrus spp.), but the underlying molecular mechanism has not been characterized. In this study, ethylene induced the expression of PpERF105, which encodes a transcription factor. PpERF105 functioned as a transcriptional activator, but it inhibited anthocyanin biosynthesis in pear. A transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 57 publications
(106 reference statements)
2
78
0
Order By: Relevance
“…Results in tables 2,3 and 4 showed that the compote cultivar records the lowest values (P≤0.05) of weight loss (1.59 and 3.78%), total acidity (0.87 and 1.41%), peroxidase enzyme activity (2.53 and 1.84 absorbing unit/minute/ml) for both study seasons, chlorophyll b (0.09 mg/ml) and total chlorophylls (0.17 mg/ml) for second season, whereas it records the highest values of fruit firmness (14,13 and 20.42 Kg/cm 2 ), total sugars (16.72 and 12.26%), TSS (12.90 and 13.00%) for both seasons, a, b and total chlorophylls and total carotenoids (0.08, 0.14, 0.22 and 0.09 mg/ml) for first season compared to spadona cultivar. Although, the time of fruit maturing and remaining on trees was different between spadona and compote cultivars; June for spadona and October for compote (Table 1), most of the differences in characteristics of the two studied cultivars are controlled by genetic factors [18] as a result of differences in internal hormones, enzyme activities, and fruit structure, where fruits with more cells density and less internal spaces are firmer [19,20], which reflects on the characteristics of the cultivars of the same species to a significant level, as shown in weight loss, fruit firmness and total sugars (Table 3 and 4). Regarding ripening treatments, from the results of the same tables, it appears that the control had the slower ripening process for both seasons where it recorded the lowest values of weight loss (0%), total sugars (12.11 and 8.55%), TSS (11.90 and 11.77%), peroxidase enzyme activity (2.50 and 2.38%) and total carotenoids (0.04 and 0.14 mg/ml) compared to other ripening treatments that record highest values significantly of fruits firmness (14.97 and 19.00 Kg/cm 2 ), total acidity (1.59 and 1.83 %) and total chlorophylls (0.27 and 0.38 mg/ml) for both seasons respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Results in tables 2,3 and 4 showed that the compote cultivar records the lowest values (P≤0.05) of weight loss (1.59 and 3.78%), total acidity (0.87 and 1.41%), peroxidase enzyme activity (2.53 and 1.84 absorbing unit/minute/ml) for both study seasons, chlorophyll b (0.09 mg/ml) and total chlorophylls (0.17 mg/ml) for second season, whereas it records the highest values of fruit firmness (14,13 and 20.42 Kg/cm 2 ), total sugars (16.72 and 12.26%), TSS (12.90 and 13.00%) for both seasons, a, b and total chlorophylls and total carotenoids (0.08, 0.14, 0.22 and 0.09 mg/ml) for first season compared to spadona cultivar. Although, the time of fruit maturing and remaining on trees was different between spadona and compote cultivars; June for spadona and October for compote (Table 1), most of the differences in characteristics of the two studied cultivars are controlled by genetic factors [18] as a result of differences in internal hormones, enzyme activities, and fruit structure, where fruits with more cells density and less internal spaces are firmer [19,20], which reflects on the characteristics of the cultivars of the same species to a significant level, as shown in weight loss, fruit firmness and total sugars (Table 3 and 4). Regarding ripening treatments, from the results of the same tables, it appears that the control had the slower ripening process for both seasons where it recorded the lowest values of weight loss (0%), total sugars (12.11 and 8.55%), TSS (11.90 and 11.77%), peroxidase enzyme activity (2.50 and 2.38%) and total carotenoids (0.04 and 0.14 mg/ml) compared to other ripening treatments that record highest values significantly of fruits firmness (14.97 and 19.00 Kg/cm 2 ), total acidity (1.59 and 1.83 %) and total chlorophylls (0.27 and 0.38 mg/ml) for both seasons respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al 15 found VvMYBC2L2 gene weakly expressed during the fruit development in grapevine, it suggested that VvMYBC2L2 gene played a role as a negative function of anthocyanin biosynthesis. Ni et al 22 studied that Ethylene-activated PpERF105 induced the expression of PpMYB140 to inhibit anthocyanin biosynthesis, and then the PpMYB140 gene played a negative function in red pear fruit. The results of these studies are consistent with the results of this study, suggesting that VvMYBB1 gene and VvMYBA3 gene have a negative effect on the formation of grape skin color of 'Yatomi Rose' grape.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that in addition to structural genes directly acting on the flavonoid pathway, most miRNA can indirectly participate in the regulation of flavonoid biosynthesis by target transcription factors (Table 2). With further research on transcription factors in plants, it has been found that they individually or jointly regulate flavonoid metabolism and respond to various biotic and abiotic stresses (Xu et al 2015;Ni et al 2021). In A. thaliana, most genes in the metabolic pathway of phenylpropane are regulated by MBW.…”
Section: Mirna-targeted Transcription Factor Regulates the Flavonoid Pathwaymentioning
confidence: 99%
“…The role of MYB111 in response to salt stress is speculated to be achieved primarily through its regulation of flavonoid biosynthesis (Li et al 2019). Ethylene-activated Pp ethylene response factor 105 (PpERF105) induces expression of the repressor-type R2R3-MYB gene PpMYB140 to inhibit anthocyanin biosynthesis in red pear fruit (Ni et al 2021). Although some miRNAs have been reported to be associated with abiotic stress responses in plants, systematic studies on stress-related miRNAs and their targets in plants remain limited.…”
Section: Environmental Factor-mediated Mirnas Involved In Flavonoid B...mentioning
confidence: 99%